2004
DOI: 10.1063/1.1641520
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN current aperture vertical electron transistors with regrown channels

Abstract: AlGaN/GaN current aperture vertical electron transistors with regrown aperture and source regions have been fabricated and tested. A 2 μm thick GaN:Si drain region followed by a 0.4 μm GaN:Mg current-blocking layer were grown by metalorganic chemical vapor deposition on a c-plane sapphire substrate. Channel apertures were etched, and a maskless regrowth was performed to grow unintentionally doped GaN inside the aperture as well as above the insulating layer, and to add an AlGaN cap layer. Cl2 reactive ion etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
58
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(61 citation statements)
references
References 11 publications
0
58
0
Order By: Relevance
“…Free-standing GaN substrates with a low dislocation density are now commercially available [4], allowing the study of vertical GaN-based transistors on GaN substrates possible. Thus far, vertical insulated gate HFETs with re-grown current aperture [3,5] and vertical trench gate metal oxide semiconductor field effect transistors (MOSFETs) [6,7] have been reported. However, their insufficient specific onresistance and breakdown voltages as well as the difficulty of normally-off operation in the insulated gate HFET hamper the practical realization of these devices for power electronics applications.…”
mentioning
confidence: 99%
“…Free-standing GaN substrates with a low dislocation density are now commercially available [4], allowing the study of vertical GaN-based transistors on GaN substrates possible. Thus far, vertical insulated gate HFETs with re-grown current aperture [3,5] and vertical trench gate metal oxide semiconductor field effect transistors (MOSFETs) [6,7] have been reported. However, their insufficient specific onresistance and breakdown voltages as well as the difficulty of normally-off operation in the insulated gate HFET hamper the practical realization of these devices for power electronics applications.…”
mentioning
confidence: 99%
“…Even though, this is one of the advantageous designs for high power device, vertical technology is not mature yet. Yaacov et al has reported the current aperture vertical electron transistor (CAVET) [9]; this report shows that the high electric field region being buried inside the bulk of material which is advantageous to mitigate the DC-RF dispersion. Previous reports successfully prove that III-V vertical device has potential of low value of on-state resistance (R on ) [10], high speed device [11] and very high breakdown voltage [12,13].…”
Section: Introductionmentioning
confidence: 96%
“…The electric field at the surface, which results from the small potential difference between the gate and the source, is relatively small, so the surface states should not fill up with electrons. Thus, DC-RF dispersion in vertical HEMT is reduced [11]. For these reasons, the GaN-based vertical transistor has become an attractive alternative for power devices.…”
Section: Introductionmentioning
confidence: 99%